Radiographic progression and survival of the different HRCT patterns of idiopathic pulmonary fibrosis - Mura, Marco; Rellini, Carlotta; Taha, Nada; Sbordone, Francesco Paolo; rufi, flavia; montesanto, francesca; Floris, Roberto; Zompatori, Maurizio; Sergiacomi, Gianluigi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Introduction. Idiopathic pulmonary fibrosis (IPF) is a chronic disease with typical HRCT patterns, but biopsy can show IPF in patients with atypical patterns. It is unknown how progression pattern varies among different radiographic presentations of IPF. The aim of this study was to investigate the longitudinal radiographic evolution of typical and non-typical patterns and to compare progression of disease among different presentation HRCT patterns. Materials and Methods. One-hundred-twenty-three consecutive patients diagnosed with IPF in 2 tertiary referral hospitals were included in the study. Longitudinal evolution of non-typical patterns was considered. The HRCT visual fibrosis score was used as a reliable evaluation tool of disease progression. All HRCTs were scored by 2 senior chest radiologists with ILD expertise. The primary endpoint was the evolution of the presentation pattern to probable or typical. The secondary endpoint was lung transplant (LTx)-free survival from the time of diagnosis. Results. Average interval between HRCTs was 16±5 months; average follow-up after the 2nd HRCT was 17±11 months. Four out of 45 (8.9%) patients with probable pattern “evolved” to a typical pattern of IPF, while 5 out of 31 (16.1%) with indeterminate/alternative pattern “evolved” to probable pattern. An average HRCT fibrosis score increase of 9±11% was observed with typical (n=49), 6±5% with probable (n=43) and 7±8% (n=31) with indeterminate/alternative presentation pattern. LTx-free survival did not show differences related to presentation HRCT patterns.